2021
DOI: 10.1177/17588359211059896
|View full text |Cite
|
Sign up to set email alerts
|

Newly developed dual topoisomerase inhibitor P8-D6 is highly active in ovarian cancer

Abstract: Background: Ovarian cancer (OvCa) constitutes a rare and highly aggressive malignancy and is one of the most lethal of all gynaecologic neoplasms. Due to chemotherapy resistance and treatment limitations because of side effects, OvCa is still not sufficiently treatable. Hence, new drugs for OvCa therapy such as P8-D6 with promising antitumour properties have a high clinical need. The benzo[ c]phenanthridine P8-D6 is an effective inductor of apoptosis by acting as a dual topoisomerase I/II inhibitor. Methods: I… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…A major requirement for drug effectiveness is that the drug reaches its nuclear target structure-DNA-topo I and II complex. In addition to previous studies on colon cancer and ovarian cancer cells [ 5 , 19 ], this study confirms the localization of P8-D6 in the cytoplasm and the nucleus of BC cells after treatment ( Figure 2 A–C). It was determined that P8-D6 reached the cell nucleus by quantifying the fluorescence intensity per nuclear area ( Figure 2 C, Supplementary Figure S1B,C ) In addition, the colocalization of P8-D6 and topo I was detected by fluorescence staining ( Figure 2 (Aii), Supplementary Figure S1A ).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…A major requirement for drug effectiveness is that the drug reaches its nuclear target structure-DNA-topo I and II complex. In addition to previous studies on colon cancer and ovarian cancer cells [ 5 , 19 ], this study confirms the localization of P8-D6 in the cytoplasm and the nucleus of BC cells after treatment ( Figure 2 A–C). It was determined that P8-D6 reached the cell nucleus by quantifying the fluorescence intensity per nuclear area ( Figure 2 C, Supplementary Figure S1B,C ) In addition, the colocalization of P8-D6 and topo I was detected by fluorescence staining ( Figure 2 (Aii), Supplementary Figure S1A ).…”
Section: Resultssupporting
confidence: 89%
“…To investigate the toxicity of P8-D6, we determined the hepatotoxicity of P8-D6 on human hepatocytes in previous studies and tested P8-D6 on non-tumor-associated ovarian epithelia cells. In that analysis, the cell integrity in non-cancer cells was slightly affected, and no hepatotoxic effect was detected in in vitro studies [ 19 ]. In characterizing the mechanism of action of P8-D6, it was previously shown that it acts as a dual topo inhibitor [ 5 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A new promising compound for OC therapy is the dual topoisomerase inhibitor P8-D6. P8-D6 was investigated as a single-drug in in vitro studies in a translational approach and showed high antitumoral efficacy [8,9]. P8-D6 is an inductor of apoptosis by acting as a dual topoisomerase poison.…”
Section: Introductionmentioning
confidence: 99%
“…P8-D6 is an aza-analogous Benzo[c]phenanthridine with cytotoxic properties [17]. Its high efficacy in the therapy of OC and breast cancer was recently demonstrated in 2D monolayer cell culture and spheroids [8,9].…”
Section: Introductionmentioning
confidence: 99%